2019
DOI: 10.1136/bmjopen-2018-025348
|View full text |Cite
|
Sign up to set email alerts
|

Causes of albuminocytological dissociation and the impact of age-adjusted cerebrospinal fluid protein reference intervals: a retrospective chart review of 2627 samples collected at tertiary care centre

Abstract: ObjectiveWe set out to test the discriminative power of an age-adjusted upper reference limit for cerebrospinal fluid total protein (CSF-TP) in identifying clinically relevant causes of albuminocytological dissociation (ACD).MethodsWe reviewed the charts of 2627 patients who underwent a lumbar puncture at a tertiary care centre over a 20-year period. Samples with CSF-TP above 45 mg/dL (0.45 g/L) were included. Samples with white cell count >5×109/L, red cell count >50×109/L and glucose <2.5 mmol/L (45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 35 publications
2
43
0
1
Order By: Relevance
“…These include, but are not limited to, male sex, body mass index, diabetes mellitus, hypothyroidism, hypoparathyroidism, Cushing’s disease, uremia, medications (such as phenytoin and phenothiazines) [ 287 , 288 ]. Elevated CSF protein has been observed in a wide range of neuropsychiatric disorders and we did not document past medical/neuropsychiatric history for patients included in this review [ 288 , 289 ]. Further, though perspectives on the relationship between CSF protein and age vary, it has been suggested that CSF protein may increase with age throughout adulthood and we did not take age into consideration when we reviewed CSF protein [ [287] , [288] , [289] , [290] ].…”
Section: Discussionmentioning
confidence: 99%
“…These include, but are not limited to, male sex, body mass index, diabetes mellitus, hypothyroidism, hypoparathyroidism, Cushing’s disease, uremia, medications (such as phenytoin and phenothiazines) [ 287 , 288 ]. Elevated CSF protein has been observed in a wide range of neuropsychiatric disorders and we did not document past medical/neuropsychiatric history for patients included in this review [ 288 , 289 ]. Further, though perspectives on the relationship between CSF protein and age vary, it has been suggested that CSF protein may increase with age throughout adulthood and we did not take age into consideration when we reviewed CSF protein [ [287] , [288] , [289] , [290] ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiology of ACD is unknown, but different mechanisms have been proposed, including the intrathecal production of specific proteins (IgG and myelin basic protein), dysfunction of the bloodbrain barrier, dysfunction of the blood-nerve barrier, decreased CSF flow and sequestration of CSF in spinal cord compression. [5][6][7] In veterinary medicine, several diseases, such as idiopathic polyradiculoneuritis, extradural compressive lesions, intramedullary lesions (neoplasia and inflammatory or infectious diseases), idiopathic epilepsy, degenerative myelopathy, fibrocartilaginous embolism, trauma, vasculitis, trigeminal, facial and vestibular neuropathies have been reported to cause ACD, yet the majority of them anecdotally. 3,[8][9][10][11][12] In human medicine, several conditions have been traditionally associated with ACD including infectious and non-infectious meningoencephalitis, intra and extra-axial tumours, inflammatory polyneuropathy, hydrocephalus, angiitis of the CNS, cerebral venous sinus occlusion, optic nerve disease, facial neuritis, posterior reversible encephalopathy syndrome, structural spinal disorders, nervous system toxic exposure, dementia, epileptic seizures, strokes, intrathecal chemotherapy and subarachnoid hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…3,[8][9][10][11][12] In human medicine, several conditions have been traditionally associated with ACD including infectious and non-infectious meningoencephalitis, intra and extra-axial tumours, inflammatory polyneuropathy, hydrocephalus, angiitis of the CNS, cerebral venous sinus occlusion, optic nerve disease, facial neuritis, posterior reversible encephalopathy syndrome, structural spinal disorders, nervous system toxic exposure, dementia, epileptic seizures, strokes, intrathecal chemotherapy and subarachnoid hemorrhage. 6,13,14 In human medicine, the reported ACD prevalence is 31.4-31.8%, both analysed in large cohorts of patients with CSF collected in the LSS and using the traditional 45 mg/dL reference limit for TP concentration. 6,15 In veterinary medicine, there are no studies analysing the different causes and prevalence of ACD, and therefore it is unknown which diseases can disrupt the blood brain barrier enough to cause a leakage of proteins without affecting the cell count.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, her findings of CSF albuminocytological dissociation were initially felt to corroborate a diagnosis of GBS, though this finding is relatively non-specific and can be seen with various inflammatory aetiologies. 8 Our patient’s experience was therefore instructive in showing that paraneoplastic polyneuropathy may overlap clinically with GBS, with regard to both symptomatology and lab findings. A similar initial misdiagnosis of GBS in a patient with ANNA-1-associated sensorimotor neuropathy has been previously reported, though this patient also had brain MRI findings of limbic encephalitis that suggested a paraneoplastic aetiology.…”
Section: Discussionmentioning
confidence: 92%